Baby knows best? The impact of weaning style on food preferences and body mass index in early childhood in a case–controlled sample - Townsend, Ellen; Pitchford, Nicola J. (BMJ Publishing Group: BMJ Open, 2012)
Objective The impact of different weaning methods on food preferences and body mass index (BMI) in early childhood is not known. Here, we examine if weaning method—baby-led weaning versus traditional spoon feeding—influences food preferences and health-related outcomes.